Effect of fucoidan on kidney injury in type 2 diabetic rats based on PI3K/AKT/Nrf2. (March 2022) - Huang, Haoyue; Liu, Yaping; Xu, Ze; Zhang, Dongdong; Feng, Mingming; Zhao, Tong; Zhang, Luoya; Li, Wenjie; Li, Xing
Graphical abstract: Abstract: Diabetic nephropathy (DN) is the most serious complication of diabetes mellitus. Although some studies have demonstrated that fucoidan can improve DN, the specific protective mechanism is not fully understood, so this study investigated the improvement effect and possible mechanism of fucoidan on renal function in type 2 diabetic (T2D) rats. The results showed that fucoidan could improve the general symptoms and disorders of glucolipid metabolism in T2D rats after 8 weeks of intervention. And it could alleviate the kidney damage in T2D rats. Meanwhile, fucoidan could reduce the oxidative stress levels in the blood and kidney of T2D rats, and significantly improved the expression levels of corresponding proteins (PI3K, AKT, Nrf2, HO-1, NQO1, TGF-β1) in the kidney tissues. The above results suggested that fucoidan could improve renal injury in T2D rats through antioxidant, and the mechanism may be related to the activation of PI3K/AKT/Nrf2.